The Success Case Method: A Simple Evaluation Tool to Identify Critical Success Factors and Program Impa - Bell, Catherine; McDonalds, Diane (Australian Evaluation Society Inc., 2006)
Identification and reporting of critical success factors and program i mpact in an efficient, yet comprehensive manner is an inherent difficu lty facing many evaluators of large-scale evaluations. This paper deta ils how two evaluators encountered such problems in the initial review of a large-scale initiative and then successfully addressed these iss ues through the application of the Success Case Method in a subsequent evaluation of the same program. The Success Case Method is a down-to- earth evaluation tool that can be used for: finding out what is workin g and what is not, which also provides accurate and trustworthy inform ation that can be used to make timely decisions (Brinkerhoff, 2003, p. 3). This paper reports on the advantages of applying this approach to the evaluation of the Primary Welfare Officer Initiative (PWOI), a pro gram that aims to improve the capacity of schools to support students at risk of disengagement and who are not achieving their educational p otential.